27 Rationale and design of the effect of mineralocorticoid receptor antagonist therapy in patients with acute myocardial infarction or injury and non-obstructive coronary arteries: a registry-based, stratified-medicine, randomised, controlled trial. (28th January 2023) - Sykes, Robert; Morrow, Andrew; Abouzaid, Ahmed Mahrous; Ang, Daniel; Apps, Andrew; Bradley, Conor; Brogan, Richard; Carberry, Jaclyn; Cleland, John; Collison, Damien; Eteiba, Hany; Ghattas, Angie; et al.
Abstract : Conflicts of Interest: Professor Colin Berry is employed by The University of Glasgow, which holds research and consultancy agreements with Abbot Vascular, AstraZeneca, Coroventis, GSK, HeartFlow, Menarini, Neovasc, Novartis, Siemens Healthcare and ValoHealth. These companies had no involvement in this manuscript. The other authors do not have any potential conflicts of interest. Support Statement: Professor Berry is supported by a British Heart Foundation Centre of Research Excellence award (RE/18/6134217) and funding from the Chief Scientist Office, UKRI (COVID-HEART, reference MC/PC/20014), EPSRC (EP/N014642/1; EP/S030875/1) and Wellcome Trust. Dr Andrew Morrow is supported by research funding from the Medical Research Council (MR/S018905/1). Dr Kenneth Mangion is supported by research funding from the Chief Scientist Office (COV/LTE/20/10, COV/GLA/20/05). Abstract: Background: Myocardial infarction and non-obstructive coronary arteries (MINOCA) affects 1 in 9 patients with acute coronary syndrome. Vascular pathophysiology includes atherothrombosis and coronary vasomotion disorders. MINOCA has an unmet therapeutic need. Objectives: To implement stratified medicine in patients with MINOCA by undertaking a prospective, registry-based, randomised, blinded end-point trial. Rationale: There are no evidence-based, disease-modifying therapies for patients with MINOCA. Preventive therapy with antiplatelet drugs and statins is empirical. Coronary microvascular dysfunction, including increased microvascular resistance, impaired vasodilator reserve and vasospasm, is implicated in the pathogenesis of MINOCA. Targeted therapy may reduce myocardial injury, improve myocardial recovery and health status prospectively. The rationale is for a stratified medicine approach targeting microvascular dysfunction with eplerenone, a vasculoprotective mineralocorticoid receptor antagonist, in MINOCA patients with coronary microvascular dysfunction. Design: Following informed consent, 350 patients with MINOCA will be prospectively enrolled (NCT05198791 ) into a registry. Coronary microvascular function will be measured during invasive angiography. Eligible patients with one or more cardiovascular risk factors and elevated index of microvascular resistance (IMR ≥25) will be randomised to receive eplerenone or standard care (n = 150) in a prospective randomised open blinded end-point design. All patients will undergo the same assessments including cardiovascular magnetic resonance imaging (MRI) within two weeks of enrolment to establish a final diagnosis. Trial patients will also be invited to undergo repeat MRI with adenosine stress perfusion at six months. Primary outcome: Registry: the proportion of patients with MINOCA and IMR ≥25; Trial: Within-subject change in NT-proBNP at pre-defined measurement time-points: baseline, 1 and 6 months. Secondary outcomes: Global hyperaemic myocardial blood flow (ml/min/g tissue); patient reported outcome measures and quality of life questionnaires; health-economics questionnaires, within-subject change in markers of collagen degradation as a marker of myocardial fibrosis vascular adhesion molecules as markers of vascular inflammation. Intravascular imaging with optical coherence tomography (OCT) will be undertaken in a sub-study (n=30). Participants will be invited to take part in a vascular sub-study, undergoing gluteal subcutaneous fat biopsy to isolate and characterise small resistance artery biology. Value: Novel data on stratified medicine for MINOCA and eplerenone as potential disease-modifying therapy for this condition.